Development and Validation of the Socio-Ecological Scale for Identifying Delays in Treatment for Breast Cancer Patients - Sadia Jabeen; Rubeena Zakar; Florian Fischer (International Journal of Breast Cancer)
Conclusions: It can be concluded that this scale is a valuable addition to assess the underlying factors of delayed presentation in patients with breast cancer in the context of the socio-ecological model in Pakistan.